MEMAKNAI PENDIDIKAN SEBAGAI PROYEK MORAL, INTELEKTUAL, DAN SPRITUAL (ANALISIS KRITIS PENAFSIRAN Q.S. AL-MUJADILAH AYAT 11) - Muhammad Yusuf; Mardan Mardan (Universitas Muhammadiyah Metro, 2022)
The education process often produces a dichotomy between moral, intellectual, and spiritual aspects, even though education can make all these aspects simultaneously and in balance. This article is an analytical study of the meaning of verse 11 of Surah al-Mujadilah regarding education that integrates moral, intellectual, and spiritual competencies. Data are tracked and collected from the interpretation of the ulama through books of tafsir, the preachers' explanations, and relevant articles. The analysis was carried out by applying the approach to the sciences of the Koran, the science of interpretation, and educational theory. The understanding of verse 11 surah al-Mujadilah is distorted because of the limited interpreters' competence personally and intellectually and the selection of an inappropriate method of interpretation. The neglect of the moral urgency in education has led to a moral crisis among intellectuals and educated people. The ethical problem is not only happening to ordinary people but also intellectuals. As a result, modern humans who are synonymous with scientific progress are moving towards moral destruction. If morals are broken, it has a destructive impact on the whole.Keywords: Critical Analysis of Education, Intellectual Education, Moral Education